2019
DOI: 10.1111/cid.12824
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical comparison of two different allogeneic bone grafting materials for alveolar ridge reconstruction: A prospective randomized trial in humans

Abstract: BackgroundPreclinical studies have hypothesized a possible immunological reponse to allogeneic materials due to detection of remnants of potential immunogenic molecules. However, their impact on integration, bone remodeling and immunological reaction after the augmentation procedure is largely unknown and a direct correlation of analytical data and evaluation of human biopsies is missing.PurposeThe present study aimed to compare two commercially available allogeneic materials regarding their content of cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…No evidence of acute or chronic inflammation was observed in any of the samples. Solakoglu et al also demonstrated no signs of inflammatory reactions with using allogenic bone materials 27 . In the present study, all biopsies were prepared form the buccal region of the augmented ridge; thus, the probability of native bone existence in prepared biopsies decreased.…”
Section: Discussionmentioning
confidence: 42%
“…No evidence of acute or chronic inflammation was observed in any of the samples. Solakoglu et al also demonstrated no signs of inflammatory reactions with using allogenic bone materials 27 . In the present study, all biopsies were prepared form the buccal region of the augmented ridge; thus, the probability of native bone existence in prepared biopsies decreased.…”
Section: Discussionmentioning
confidence: 42%
“…The follow-up period after ridge augmentation or implant placement was reported in all studies except two [16,35], and it ranged from 3.1 months to 10 years. Two studies excluded smokers [30,38], 14 studies reported periodontal status of subjects [16-18, 21-23, 25-30, 35, 36, 40-43], and excluded subjects with untreated periodontal disease, or with a full mouth plaque score and full mouth bleeding score of more than 25%.…”
Section: Study Design and Characteristicsmentioning
confidence: 99%
“…The analysis of this work used histomorphometry and immunohistochemistry, these methodologies are widely used to assess cell tissue components involved in the osseointegration and bone remodeling process. [13][14][15][16] The results of the present study showed that the synthetic nano-HA/ß-TCP mixture biomaterial used to fill calvarial bone defects in a rat model induced a better cell response than deproteinized bovine bone mineral (DBBM). Nano-HA/ß-TCP mixture showed larger percentages of stained areas with Masson's trichrome, PAS, MMP-9, and TNF-α than DBBM biomaterial.…”
Section: Discussionmentioning
confidence: 74%